Сучасний стан організації білінгвальної освіти для національних меншин в Австрії - Боднарчук, Тетяна (Studies in Comparative Education, 2013)
У статті проаналізовано сучасний стан організації білінгвальної освіти для дітей національних меншин, які проживають на території Австрії. Розглянуто особливості функціонування двомовних шкіл для дітей різних національних меншин, основні тенденції їх розвитку та проблеми, які пов’язані з організацією навчального процесу. В статье проанализирована современная организация билингвального образования для детей национальных меньшинств, которые проживают на территории Австрии. Рассмотрены особенности функционирования двуязычных школ для детей разных национальных меньшинств, основные тенденции их развития и проблемы, связанные с организацией учебного процесса. Austria is a multinational country, for this reason the problem of bilingual education for national minorities is of great importance. The aim of this article is to analyze the organization of bilingual education for national minorities in Austria with the perspective of introduction of Austrian progressive ideas into Ukrainian schools. Because of the fact that every national minority has its historical and cultural traditions which influence the attitude of its representatives to native language schools, it is worth analyzing it for each minority individually. Education for Slovenes in Carinthia develops in three variants: full circle (1–12 classes) with the perspective of getting bilingual vocational and high (major, bachelor) education; in schools with bilingual classes at all levels of compulsory education; studying the native language at all levels. There are 60 German-Slovene primary schools, 1 compulsory and 1 secondary school, 2 professional schools. Bilingual education for Croats in Burgenland follows the same way except professional education. There exist German-Croatian schools: 34 primary schools, 7 compulsory and 2 secondary schools. Bilingual education for Hungarians is characterized by the attempt of returning the native language education to the territories where this minority lives. As for bilingual education for the rest of minorities (Czech, Slovak etc.) living in the capital and federal land Wien, there is not any legislative regulations for functioning of bilingual schools. Still bilingual schools for children of this national minority exist for a long period but only as private ones. In Ukraine like in Austria we also find some problems in management of bilingual educational process. That raises the necessity to study the experience of multinational countries where these issues are solved successfully, to draw the scientific attention to carrying out the educational materials for bilingual schools, to study and spread the experience of bilingual schools.